Persepsi Guru dan Siswa terhadap Pelaksanaan Program Makan Bergizi Gratis dalam Meningkatkan Kehadiran siswa di SDN inti Sungai Miai 11 - Risda; Hamidah; Nur Ramadhanianti; Muhammad Qolbi; Ahmad Suriansyah; Maimunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe teachers’ and students’ perceptions of the implementation of the Free Nutritious Meal Program (MBG) and its influence on student attendance at SDN Inti Sungai Miai 11. Using a qualitative case study approach through interviews, observations, and document analysis, the findings show that the MBG program positively contributes to students’ health, motivation, and school attendance. Teachers and students reported that the program helps fulfill daily nutritional needs, enhances learning focus, and increases enthusiasm for attending school, while also reducing the economic burden on low-income families. Despite these benefits, challenges remain, including limited funding, menu variation, and the lack of nutrition specialists. Overall, the MBG program is considered effective in improving student attendance and supporting equitable access to nutrition in elementary schools.